Pentingnya Asesmen Diagnostik Kognitif dalam Pembelajaran Matematika - Eka, Firmina; Sugiatno, Sugiatno; Yani T, Ahmad; Siregar, Nurfadilah; Meldi, Nadya Febriani (Universitas Sultan Ageng Tirtayasa, 2025)
ABSTRACTThis study discusses the importance of cognitive diagnostic assessment in Mathematics learning. Assessment is needed to determine students' prerequisite understanding before learning new material, considering the interrelated mathematical concepts. This study uses a qualitative method with a literature study to collect information on the application of diagnostic assessment in the Independent Curriculum. The results of the study indicate that mastery of prerequisite material has a significant effect on students' mathematical literacy skills. Students who have a good understanding of basic mathematical concepts tend to find it easier to understand advanced material. This study concludes that cognitive diagnostic assessment should be applied routinely to help educators design learning that suits students' needs. ABSTRAKPenelitian ini membahas pentingnya asesmen diagnostic kognitif dalam pembelajaran Matematika. asesmen diperlukan untuk mengetahui pemahaman prasyarat peserta didik sebelum mempelajari materi baru, mengingat konsep matematika yang saling berkaitan. Penelitian ini menggunakan metode kualitatif dengang studi kepustakaan untuk mengumpulkan informasi mengenai penerapan asesmen diagnostik dalam Kurikulum Merdeka. Hasil penelitian menunjukkan bahwa penguasamateri prasyarat berpengaruh signifikan terhadap kemampuan literasi matematis peserta didik. Peserta didik yang memiliki pemahaman yang kuat tentang konsep dasar matematika cenderung lebih mudah dalam memahami materi lanjut. Penelitian ini menyumpulkan bahwa asesmen diagnostik kognitif harus diterapkan secara rutin untuk membantu pendidik merancang pembelajaran yang sesuai kebutuhan peserta didik.